Causes of Household Fires in Rural Areas: an Exploratory Research - Maybelle Paulino; Lloyd Matthew Paulino (PT FORMOSA CENDEKIA GLOBAL, 2023)
Household fire is a societal problem. Much has been known about the causes of fires; however, little is known about the causes of rural fires. This research addresses this gap in the fire-related literature by delineating the causes of household fires in rural areas. Data were drawn from 30 household members who participated in the online interviews. The data gathered were analyzed using a thematic analysis. The results show that the most common causes of rural household fires are incidental fires, electricity, candles, appliances, building materials, human error, and human behavior. The findings of this study may serve as supplements for crafting fire prevention strategies and intervention programs for households in rural areas.